Strengthening of steel plates subjected to uniaxial compression using small-diameter CFRP strands. (15th May 2016) - Kazem, Hamid; Guaderrama, Lucas; Selim, Hatem; Rizkalla, Sami; Kobayashi, Akira
Highlights: Small-diameter CFRP strands for strengthening steel structures eliminate de-bonding. High-modulus CFRP strands provide the best system for plates under compression. Effectiveness of the strengthening system increases by increasing slenderness ratio. Increasing reinforcement ratio increases the buckling capacity of steel plate. Abstract: This paper presents the results of a study that was carried out to investigate the use of small-diameter CFRP strands for strengthening steel plates subjected to uniaxial compression. This study is part of a comprehensive research program to evaluate the use of the small-diameter CFRP strands for shear strengthening of steel girders. The research in this paper was undertaken to examine the bond characteristics of the proposed material which is expected to eliminate the debonding failure observed for CFRP laminates strengthening system and to resist the compressive stresses induced in high shear zones. The small-diameter CFRP strands are stitched together with a gap between the strands to allow each strand to be completely covered by the adhesive material. The effectiveness of the strengthening system was investigated by varying various parameters believed to affect the overall behavior including the slenderness ratio of the steel plates as well as mechanical properties and reinforcement ratios of the CFRP strands. Strengthened plates exhibited higher buckling capacity in comparison to similar plates without CFRP strands. In addition, the small-diameter CFRP strands did not show any signs of debonding at large lateral deformation associated with elastic buckling.